Booklet “Prevention against trachoma”: An experience report (Research, Society and Development, 2021)
Introduction: Trachoma is an infectious contagious disease, caused by the bacterium Chlamydia Trachomatis, whose risk factors are unhealthy conditions, poor hygiene, poor sanitation, water supply and low socioeconomic status. Trachoma is classified as one of the neglected diseases that most concern health authorities, but of little relevance in treatments due to the low profitability provided for solving this disease. Thus, there is a need for more investments in Health Education at the UBS, since health promotion and prevention are the best ways to avoid trachoma in regions with a low level of basic sanitation. Methodology: Descriptive study, of the experience report type, describing the steps in the creation of a booklet for users of the Unified Health System in the city of Parnaíba-PI, in which health information about trachoma was disseminated. Experience Report: The experience of preparing a booklet as medical students were enriching, as it allowed them to experience the academic extension process, as well as providing the population with information about trachoma, with the aim of improving regional epidemiological indicators. Final Considerations: With the approach used, we seek to positively impact society in the health sphere. Furthermore, it will be edifying to establish a bond between future health professionals and their potential patients. Thus, it is reinforced that technology can be integrated into health promotion, due to the potential to disseminate information and change the behavior of society.